Vitamin D Supplementation Dose as The Prevention of Fragility Fracture In Chronic Kidney Disease Patient: A Systematic Review - Aldico J Sapardan; Rashida S Djatnika (Jurnal Sehat Indonesia (JUSINDO), 2024)
CKD affects more than 10% of the global population. It can cause osteoporosis and increase the risk of fractures, especially as CKD becomes more serious. In CKD, mineral and bone disorders (CKD-MBD) cause abnormalities in how the body processes vitamin D, calcium, phosphorus, or parathyroid hormone (PTH). It can also affect bone strength and cause calcium build-up in the soft tissues. Treatment usually starts with correcting the chemical abnormalities that occur in the body due to CKD-MBD before focusing on osteoporosis and fractures. A study review spanning 2010 to 2023 investigated optimal vitamin D supplementation doses in CKD patients, indicating varied outcomes influenced by factors like dosage, duration, and population characteristics. Doses ranged from 800 to 8,000 IU/day of cholecalciferol, with recommendations contingent on serum 25(OH)D levels.